2009
DOI: 10.1002/jgm.1363
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of epithelial Na+ channels by antisense oligonucleotides for the treatment of Na+ hyperabsorption in cystic fibrosis

Abstract: Background Cystic fibrosis (CF) respiratory epithelia are characterized by a defect Cl − secretion and an increased Na + absorption through epithelial Na + channels (ENaC). The present study aimed to find an effective inhibitor of human ENaC with respect to replacing amiloride therapy for CF patients. Therefore, we developed specific antisense oligonucleotides (AON) that efficiently suppress Na + hyperabsorption by inhibiting the expression of the α-ENaC subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…To evaluate effects on the function of the ENaC channel, we turned our attention to electrophysiological measurements in human nasal epithelial cells, a system which has previously been used successfully to study the effects of ENaC-targeting ASOs on the function of the channel. 5 Therefore, when human nasal epithelial cells are grown as monolayers and placed in modified Ussing chambers, it is possible to measure changes in transepithelial current through the ENaC channel. Using this system, we were able to demonstrate that GSK2225745-induced suppression of ENaCα mRNA was also associated with marked inhibition of ENaC channel function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate effects on the function of the ENaC channel, we turned our attention to electrophysiological measurements in human nasal epithelial cells, a system which has previously been used successfully to study the effects of ENaC-targeting ASOs on the function of the channel. 5 Therefore, when human nasal epithelial cells are grown as monolayers and placed in modified Ussing chambers, it is possible to measure changes in transepithelial current through the ENaC channel. Using this system, we were able to demonstrate that GSK2225745-induced suppression of ENaCα mRNA was also associated with marked inhibition of ENaC channel function.…”
Section: Discussionmentioning
confidence: 99%
“…Similar data have previously been published from studies in human-cultured nasal epithelial cells. Therefore, Sobczak and colleagues 5,19 evaluated the effects of an ASO targeting the α-subunit of ENaC. They reported that this ASO was able to significantly inhibit the function of the ENaC channel with duration of action of at least 3 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since ENaC activation has been shown to depend on several trypsin-family serine peptidases [51,52], therapeutic approaches based on protease inhibitors are also being pursued [53]. Another approach to selectively downregulate ENaC involves usage of small interference (si) RNAs to downeregulate its expression levels [54][55][56] and, given the rapid developments in siRNA therapeutics targeted to the lung [57], this strategy may become feasible in the shortterm. However, since ENaC cannot be fully blocked, given the associated risk of hypotension and other symptoms associated with psuedohypoaldosteronism (PHA1), all ENaC targeted therapies must might under tight control.…”
Section: Manipulating Other Ionic Conductances To Restore Airway Surfmentioning
confidence: 98%